Preparasi Komposit Polimer Alami Berbasis Pektin Kulit Jeruk Bali sebagai Edible Coating pada Tomat - Palungki, Anteng Relis; Auliah, Nahdatul; Imani, Nadya Alfa Cahaya (Jurnal Teknik Kimia USU, 2022)
Tomato (Solanum lycopersicum L.) is very susceptible to damage and has a relatively short shelf life. The increased production of tomatoes which are not accompanied by an increase in consumption will cause a large amount of waste. An edible coating (EC) film could increase the durability of tomatoes thus it is needed to improve the quality and shelf life of tomatoes. EC is a thin layer that is safe for consumption and environmentally friendly. In this study, EC was prepared by extracting pectin from pomelo peel combined with one of two ingredients, carboxy methyl cellulose (CMC) and tapioca, and using a plasticizer in the form of glycerol. Measurement of weight loss and organoleptic tests (color and texture) of tomatoes were carried out for 14 days. The best results were obtained by pectin 3% (w/w), CMC 1% (w/w) and tapioca 1% (w/w). The EC was able to increase the shelf life of tomatoes up to day 14 with a weight loss of 0.063%, while tomatoes without coating had been tainted on day 6 with a weight loss of 0.387%.